Implementation Of Drug Criminal Investigations At The Deli Serdang Police Region - Torang Hutapea; Hasdiana Juwita Bintang (Yayasan Multidimensi Kreatif, 2024)
This research examines the implementation of investigations into narcotics-related criminal activities within the jurisdiction of the Deli Serdang Police Department. Indonesia faces increasing challenges as both a production and distribution hub for narcotics due to its strategic position and high demand. The study highlights the rise in narcotics cases and analyzes the role of investigators in combating these crimes, as well as the obstacles they face in enforcing the law. Data collected from 2022 to 2024 shows a significant upward trend in narcotics-related cases, emphasizing the need for comprehensive strategies. This research aims to assess the effectiveness of investigative practices and identify barriers to enforcement to propose solutions for improving law enforcement outcomes.